Early Childhood Education 2019
DOI: 10.5772/intechopen.80928
|View full text |Cite
|
Sign up to set email alerts
|

Including Children with Visual Impairments in the Early Childhood Classroom

Abstract: The practice of inclusive education-or inclusion-within general education classrooms is becoming more prevalent within early childhood settings. To successfully deliver classroom curriculums, promote learner growth, and meet the goals of all students served within inclusive settings, teachers must have a basic understanding of the unique learning needs of all students, including those with visual impairments. Because students learn best when the teachers who educate them first understand their needs, this chap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…This finding from the study suggests that, it is important to empower visually impaired learners to become independent and successful. This finding corroborates the work of [14,15] who hold the view that visually impaired learners are to be empowered, however, teachers are to have basic understanding of their unique learning needs in order for such to be achieved. In other words, it is significant for teachers of visually impaired learners to know their goals, and work towards achieving them.…”
Section: Theme 3: Teaching Beyond the Curriculumsupporting
confidence: 85%
See 3 more Smart Citations
“…This finding from the study suggests that, it is important to empower visually impaired learners to become independent and successful. This finding corroborates the work of [14,15] who hold the view that visually impaired learners are to be empowered, however, teachers are to have basic understanding of their unique learning needs in order for such to be achieved. In other words, it is significant for teachers of visually impaired learners to know their goals, and work towards achieving them.…”
Section: Theme 3: Teaching Beyond the Curriculumsupporting
confidence: 85%
“…[36] took the argument a step further and found that visually impaired learners tend to rely on their senses of touch, hearing, smell, taste, movement and residual vision to gather information from their learning environments. A similar observation was made by [15], suggesting that teaching materials for students with visual impairment may not always be needed for classroom activities. Planning for the visually impaired starts with using proper lighting in order to be considerate to those learners with low vision or light sensitivity.…”
Section: Experience Of Teacherssupporting
confidence: 65%
See 2 more Smart Citations
“…Tackling visual impairment in childhood is a major global concern because it affects a child’s learning process, self-perception, life skills and overall development [ 1 ]. The World Health Organization reported in 2018 that nearly 1.3 billion people worldwide had vision impairment, the bulk of which are located in low- and middle-income countries [ 2 ].…”
Section: Introductionmentioning
confidence: 99%